Relationships between criminal law and civil law regarding the crime of theft in the Peruvian Criminal Code - Hurtado Pozo, José (2011)
In the process of interpreting and understanding the legal identities of crimes against property, the decisive aspect is related to the function given to criminal law with respect to other branches of the law, particularly to civil law. The civil or commercial factors contained in criminal laws must be understood according to the limitations, grounds and purpose of the criminal law. However, the classifications and distinctions used in civil law do not always coincide with those distinctions used in criminal law nor with the goals pursued in the relevant criminal provisions, a fact that evidences a relative autonomy between civil and criminal law.